Fluch über Akkade - Falkenstein, Adam
TCL XVI 64; TCL XVI 66; UMBS XIII 15; UMBS XIII 43; UMBS XIII 47; SRT 2; STVC 94; BE XXXI 1; SLTNi 104; SLTNi 105; SLTNi 106; SLTNi 107; SLTNi 108; SLTNi 109; STVC 111; STVC 100; STVC 101; TAD VIII2 Ni. 4155 Tf. II und X; TMHS NF III 27; TMHS NF III 28; TMHS NF III 29; TMHS NF III 30; TMHS NF III 31; TMHS NF III 32; TMHS NF III 33; STVC 135; IM 12183(a).